Administrative Tort Law: Yesterday, Today, Tomorrow - A. M. Voronov (Сибирское юридическое обозрение, 2019)
The article outlines the role and characterizes the legal idea of leading scholars of modern Russia in the context of reforming the administrative-tort legislation. The Author describes the main positions of the author, defended in the course of his work as a member of the interdepartmental working group on the preparation of the Concept of the new Code of the Russian Federation on Administrative Offenses. It is proposed to create two independent codes - the material and procedural content, the transfer of the regulation of court cases considered today in the framework of the Code of the Russian Federation on Administrative Offenses to the legislation on administrative legal proceedings, as well as cases of administrative offenses considered in the framework of arbitration proceedings. Particularly emphasized is the idea that the legislation on administrative responsibility should be normatively and logically interconnected with the legislation on the control and supervisory activity of authorities and develop in parallel with it.